If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(9 + -2x) = -90 (9 * -6 + -2x * -6) = -90 (-54 + 12x) = -90 Solving -54 + 12x = -90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + 12x = -90 + 54 Combine like terms: -54 + 54 = 0 0 + 12x = -90 + 54 12x = -90 + 54 Combine like terms: -90 + 54 = -36 12x = -36 Divide each side by '12'. x = -3 Simplifying x = -3
| 4(2z-2)=7(z+2) | | r^2+16r=0 | | 2(6+5x)=112 | | 6.6(1.2-7.3x)=16.4x+5.8 | | 4x^2=50 | | x^2-3x-3= | | t^2-6t+9=16 | | 6(-7x+4)=108 | | 4(y+3)=5(y-7) | | 7.23x+16.51=47.89-2.55x | | 4x^4+20x=0 | | y=15-4x | | r^2-25tw+5wr-5tr= | | n+3=-5n | | 13(6c-7)=8c-2 | | 2(f-7)=2f-14 | | 9z-3=9z | | 12t^3+3t=0 | | 5+x-3(x+4)=-17 | | 14d-6=7d | | 12-7=5 | | x^4-12x^2+8x+3=0 | | 30-12/3*2= | | 3x+4=-2-5x | | 5x+6=2x+2 | | -4y+7=-1 | | 7-5x=-2 | | 13x^2+15=104x | | 7a+2b=1 | | g(x)=3x+1 | | -4+7=-1 | | 2(x+3)(x-1)-x(x+3)=176 |